2018
DOI: 10.1111/vde.12713
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oral afoxolaner on naturally occurring infestations of peacocks by the louse Goniodes pavonis

Abstract: Background -Ectoparasitism of ornamental birds, including captive species kept in zoos, represents a serious health problem. Up to 13 different species of lice have been reported to affect peacocks worldwide and heavy infestation may cause anaemia. Because of this, alternatives to the prevailing treatments have been sought including use of isoxazolines. This class of drugs has been used successfully in poultry without adverse effects on health or production.Objective -To evaluate the effect of afoxolaner on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…4 The isoxazolines also have been used successfully against several ectoparasites of exotic animal species. [5][6][7] The present study was carried out with the objective of evaluating the effectiveness of lotilaner against ticks of the genus Amblyomma spp. in cane toads.…”
Section: Introductionmentioning
confidence: 99%
“…4 The isoxazolines also have been used successfully against several ectoparasites of exotic animal species. [5][6][7] The present study was carried out with the objective of evaluating the effectiveness of lotilaner against ticks of the genus Amblyomma spp. in cane toads.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a recent study demonstrated the efficacy of afoxolaner against T. canis in dogs [12]. As previously shown [12], off-label afoxolaner was demonstrated to have a very high to maximum efficacy also against lice in birds [20,21]. Another isoxazoline, fluralaner presented an efficacy of 85.1% to 100% against Linognathus setosus in dogs with follow-ups done on days 1, 7, 28 and 84 [10].…”
Section: Discussionmentioning
confidence: 57%
“…The present study is the first to evaluate the efficacy of an isoxazoline, afoxolaner, against T. canis in dogs and the first to evaluate the efficacy of afoxolaner against mammalian lice. Afoxolaner has previously been evaluated in off-label clinical studies against the chewing louse Goniodes pavonis in captive aviary birds, where it demonstrated a 100% efficacy at 28 days post-treatment in various species of pheasants [ 33 ] and an 86.6% efficacy in peacocks [ 34 ]. Kohler-Aanesen et al [ 23 ] reported an efficacy of 85.1% on day 1, 96.8% on day 7 and 100% on days 28 and 84 for an oral formulation of fluralaner against the dog sucking louse Linognathus setosus .…”
Section: Discussionmentioning
confidence: 99%